Sexual Politics and Symbolic Annihilation of Working Women in Monica Ali’s Brick Lane: A Textual Analysis - Ms. MUNAZA AKHTER (Al-Qanṭara, 2024)
The article explores the representation of female workforce in Brick Lane, both in their personal and professional capacity. The article highlights the writer’s attempt at creative placement of working women in the pink-collar jobs and in the conventionally preconceived set of skills, interests, self-perceptions, behaviors, and appearance. It also analyzes the depiction of working women’s incompetency at managing their professional and personal life on their own. The article discusses the trivialization, condemnation and omission of working women through their portrayal in the under-study novel. The analysis is based on the application of Gaye Tuchman’s theoretical concept of symbolic annihilation, and it also utilizes the ideas of Kate Millet as presented in Sexual Politics for analyzing the patriarchal power play in intimate heterosexual relationships. The analysis is divided into three sections-first section discusses depiction of working women living within Bangladesh, second section analyses portrayal of Bengali women working in London and the last section examines patriarchal politics of control within romantic and sexual relationships. The analysis utilizes Catherine Belsey’s Textual Analysis method to explore the data from the lenses of curated theoretical framework.